EFFECTIVENESS OF PBL-BASED MOBILE LEARNING TO IMPROVE STUDENTS' CRITICAL THINKING SKILLS - Irawati, Irawati; Huda, Nizlel; Adji, Sandra Sukmaning (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2022)
The purpose of this research is to evaluate whether or not students in the eighth grade at SMP Negeri 2 Betara in the Tanjung Jabung Barat Regency can improve their mathematical critical thinking skills by using mobile learning that is based on problem-based learning (PBL). The participants in this research were all eighth-graders from one junior high school in the Tanjung Jabung Barat Regency. There were a total of 128 students included in this study, and they were distributed across four classes. The sample was selected from as many as two classes, specifically VIIIA with a total of 28 students serving as the experimental group and VIIIB with a total of 28 students serving as the control group. The analysis of the data reveals that the Zcount value is 10,099, and the significance value is 0.000< 0.005; these values were determined to be significant. Therefore, the working hypothesis or alternative hypothesis that was proposed in this study is accepted. It states that there is a difference in the average critical thinking of students who use PBL-based mobile learning compared to students who use standard teaching materials. While the null or nil hypothesis, which states that